1971
DOI: 10.1111/j.1432-1033.1971.tb01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Reserve Polysaccharide of Streptococcus mitis

Abstract: The properties of a purified branching enzyme (a-l,4-glucan : a-1,4-glucan 6-glycosyltransferase) isolated from intracellular extracts of several strains of Streptococcus mitis were studied with maltodextrins, amylose, amylopectin and glycogen as substrates. Maltodextrins with an average degree of polymerization above 20 were good substrates, and the rate of branching enzyme action increased with chain-length. The enzyme had a higher affinity towards branched substrates than linear polysaccharides, and evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The B. fibrisolvens branching enzyme exhibited activity towards a wide range of oa-1,4-glucans, as has been shown for other branching enzymes (7,54,60). With amylopectin as the substrate, the B. fibrisolvens branching enzyme transferred oligosaccharide chains 5 to 10 glucose units long, with 7 as the preferred unit size.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The B. fibrisolvens branching enzyme exhibited activity towards a wide range of oa-1,4-glucans, as has been shown for other branching enzymes (7,54,60). With amylopectin as the substrate, the B. fibrisolvens branching enzyme transferred oligosaccharide chains 5 to 10 glucose units long, with 7 as the preferred unit size.…”
Section: Discussionmentioning
confidence: 78%
“…The glgB gene product catalyzes the synthesis of a-1,6-glucosidic linkages in glycogen. A number of reports have dealt with the properties and action of bacterial branching enzymes (7,12,24,54), and the enzyme from E. coli has been purified nearly to homogeneity (7). Branching enzyme activity has also been reported in a number of other bacteria (48,54,60), fungi (35), higher plants, and animals (42).…”
mentioning
confidence: 99%
“…Streptococcal pathogens contain genes required for efficient utilization of α-glucans including amylases and/or pullulanases which cleave α-1,4 and α-1,6 glycosidic bonds in starch or glycogen [14][18]. Previously, we have shown that a cell wall anchored amylopullulanase of S. suis serotype 2 ( apuA -SSU1849) was necessary to support bacterial proliferation on the α-glucan starch/pullulan (an α-1,6; α-1,4 linked glucose polymer) as a single carbon source and to promote adhesion of S. suis to porcine tracheal epithelial cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several enzymes involved in glycogen metabolism have been isolated from the soluble cell fractions of S. mitior (3,33,34). Only one phosphorylase was found among these (35).…”
mentioning
confidence: 99%